Ichthyofauna Diversity and Its Distribution in a Low-Saline Lake of Indonesia - Ahmad Muhtadi; Fredinan Yulianda; Mennofatria Boer; Majariana Krisanti; Desrita (HAYATI Journal of Biosciences, 2023)
Lake Siombak is a tidal lake that is an estuary around the lake covered with various mangrove trees. It is interesting to study the fish's spatial and temporal distribution as a unique and distinctive tidal lake ecosystem. This research was conducted for a year (from September 2018 to August 2019). Fish sampling was performed by installing gill nets (mesh size 1 inch) and cast nets (mesh size 0.5 inch). Gill nets and cast nets were installed at high and low tides during the full moon. This research showed that there were 27 species of 20 families. Tilapia, Mudskipper, Indo-pacific tarpon, and mainly Rice Fish are always found in Lake Siombak. The fish group at Lake Siombak consists of freshwater fish (mainly: Tilapia, Catfish, and Snakehead), brackish fish (mainly: Mudskipper, Rice fish, and Indo-pacific tarpon), and marine fish (mainly: Milkfish, Kanda mullet, and John's snapper). The actual resident in Lake Siombak consists of Oryziidae, Tilapia, and mudskipper. Other fish are temporary resident fish except for Lutjanidae and Scatophagidae as visitor fish during high tide and high salinity periods (dry season) and Synbranchidae during low salinity (rainy season).